Efektivitas Penerapan Model Pembelajaran Kooperatif Tipe Time Token dengan Pendekatan Problem Posing dalam Pembelajaran Matematika - Nur Aynun; Abdul Rahman; Asdar (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2019)
The purpose of this study to determine the effectiveness of time token model implementation with problem posing approach in learning mathematics in class VII SMP Negeri in Sungguminasa. The effectiveness of learning in this study is measured by the achievement of learning outcomes, student activities, and student responses to learning. This research is a pre-experiment research. The population in this research is all students of class VII of SMP Negeri 3 Sungguminasa. The sample of this study consists of one class. The sampling technique using simple random sampling. Methods of data collection using questionnaires, observations and tests. Data analysis techniques use descriptive and inferential analysis. The results of the analysis show: (1) Scores of student learning outcomes experienced a significant improvement and achieve a minimum score of 75 completeness criteria with an average scoreof student learning outcomes of 80.73. (2) Classical completeness level of 93%. (3) Student activity is in very good category. (4) The implementation of learning is in the category performed very well. (5) Student responses are in the category tend to be positive.